Development and validation of a questionnaire to measure the congenital heart disease of children’s family stressor - Yi Zhang; Hang Zhou; Yangjuan Bai; Zhisong Chen; Yanjiao Wang; Qiulan Hu; Mingfang Yang; Wei Wei; Lan Ding; Fang Ma (Frontiers in Public Health)
BackgroundFamilies of children with congenital heart disease (CHD) face tremendous stressors in the process of coping with the disease, which threatens the health of families of children with CHD. Studies have shown that nursing interventions focusing on family stress management can improve parents’ ability to cope with illness and promote family health. At present, there is no measuring tool for family stressors of CHD.MethodsThe items of the scale were generated through qualitative interviews and a literature review. Initial items were evaluated by seven experts to determine content validity. Factor analysis and reliability testing were conducted with a convenience sample of 670 family members. The criterion-related validity of the scale was calculated using scores on the Self-Rating Anxiety Scale (SAS).ResultsThe CHD Children’s Family Stressor Scale consisted of six dimensions and 41 items. In the exploratory factor analysis, the cumulative explained variance of the six factors was 61.085%. In the confirmatory factor analysis, the six factors in the EFA were well validated, indicating that the model fits well. The correlation coefficient between CHD Children’s Family Stressor Scale and SAS was r = 0.504 (p < 0.001), which indicated that the criterion-related validity of the scale was good. In the reliability test, Cronbach’s α coefficients of six sub-scales were 0.774–0.940, and the scale-level Cronbach’s α coefficient value was 0.945.ConclusionThe study indicates that the CHD Children’s Family Stressor Scale is valid and reliable, and it is recommended for use in clinical practice to assess CHD children’s family stressors.